Penerapan Good Corporate Governance Dalam Peningkatan Kinerja Bank Syariah Di Indonesia - Irmawanti Irmawanti; Mohd Winario (EL-EMIR Institute, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) in improving the performance of Islamic banks in Indonesia. GCG is regarded as an essential element in maintaining the sustainability of Islamic banking by applying the principles of transparency, accountability, responsibility, independence, and fairness in accordance with Sharia values. The research method employed is a qualitative approach using a literature review and descriptive analysis of annual reports, GCG reports, and regulations related to Islamic banking in Indonesia. The data are systematically analyzed to identify the relationship between GCG implementation and the performance of Islamic banks, both in financial and non-financial aspects. The results indicate that consistent and effective implementation of GCG can enhance the performance of Islamic banks through strengthening internal control systems, improving the quality of managerial decision-making, and increasing the trust of customers and stakeholders. In addition, the role of the Sharia Supervisory Board is proven to be significant in ensuring compliance with Sharia principles and supporting institutional performance. This study concludes that GCG is a strategic factor in promoting the sustainable performance and competitiveness of Islamic banks in Indonesia.